Pengembangan Integrasi Bangun Ruang Prisma Berbasis Etnomatika Terhadap Rumah Adat Joglo dengan Kemampuan Visualisasi Spacial pada Siswa Kelas V Sekolah Dasar - Rifky Septian Aldy; Bagus Ardi Prasetyo; Singgih Adhi Prasetyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background that prompted this research was the existence of factors in students' learning difficulties in understanding mathematics, especially in geometric material. The aim of the research is to determine the development stage and feasibility of integrating ethnomathematics-based prism spatial construction into Joglo traditional houses with spatial visualization abilities in fifth grade elementary school students. The research in this thesis uses Research and Development research using the ADDIE model. It can be concluded that the Omahku media based on ethnomathematics with visual spatial capabilities is a media that is suitable for use as a learning medium and of course can also be an alternative media used by teachers in mathematics lessons regarding spatial construction material. Based on the results of this research, the resulting learning media can provide suggestions that can be an alternative for teachers in learning, especially in building materials and can be combined with other learning resources.